2017
DOI: 10.1016/j.jcm.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the Upper Trapezius Muscle and Fascia Thickness and Strain Ratio Measures by Ultrasonography and Sonoelastography in Participants With Myofascial Pain Syndrome

Abstract: Upper trapezius thickness measurements by ultrasonography and strain ratio by sonoelastography are reliable methods in participants with myofascial pain syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 52 publications
(96 reference statements)
0
23
0
Order By: Relevance
“…Our study provides evidence of excellent reliability when using our novel estimation method for vibration-based shear wave elastography measurements of phantom elasticity and skeletal muscle stiffness. These observations are clinically important because skeletal muscle stiffness is observed in various conditions, such as myofascial pain syndrome 36 , neck and shoulder pain 27 , and low back pain 37 . Thus, our results suggest that multiple patient groups who experience muscle stiffness may benefit from our proposed method, which is a useful tool for evaluating diseases characterized by muscle stiffness and determining treatment effects; this method is expected to help reduce costs and promote introduction of vibration-based shear wave elastography in general clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Our study provides evidence of excellent reliability when using our novel estimation method for vibration-based shear wave elastography measurements of phantom elasticity and skeletal muscle stiffness. These observations are clinically important because skeletal muscle stiffness is observed in various conditions, such as myofascial pain syndrome 36 , neck and shoulder pain 27 , and low back pain 37 . Thus, our results suggest that multiple patient groups who experience muscle stiffness may benefit from our proposed method, which is a useful tool for evaluating diseases characterized by muscle stiffness and determining treatment effects; this method is expected to help reduce costs and promote introduction of vibration-based shear wave elastography in general clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The reliability of tissue stiffness assessment via ultrasound elastography as well as via myometry and indentometry has been recently documented (Pruyn et al, ; Salavati et al, ; Wilke et al, ). Because mechanoadaptation of collagenous tissues does not always go along with the adaptation of related skeletal muscles (Mersmann et al, ), it is suggested to enhance the incorporation of fascial tissue assessments in future therapeutic as well as scientific investigations in the field of sports medicine (Zuegel et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 95% of patients with chronic pain encounter Myofascial Pain Syndrome (MPS), which affects millions of individuals. It also imposes a heavy financial burden on the affected individual and society [1,2]. Approximately 54% of females and 45% of males are affected by MPS, especially due to a sedentary lifestyle and low physical activity [3].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that MPS is more prevalent in the age group of 27-50 years. MPS has been studied for more than a century; however, its diagnostic, clinical, and therapeutic aspects remain unclear [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation